Problem-Based Learning Video on Ecosystem Harmony for Social Science Subject (IPAS) in Grade 5 Elementary School Students - Kadek Emy Dhyana Putri; Anak Agung Gede Agung; Anak Agung Ayu Dewi Sutyaningsih (Jurnal Ilmiah Sekolah Dasar, 2025)
The students' poor learning outcomes can be attributed to the application of conventional teaching methods limited interactive media, and a lack of student engagement. This research was focused on fifth-grade elementary school students to develop problem-based learning video media for the topic "Harmony in Ecosystems" in Natural and Social Sciences (IPAS) lessons. This research employed quantitative methods using the ADDIE development model. Data collection methods invoved questionnaires/surveys, with data analyzed through descriptive quantitative and inferential statistical techniques. The research findings are as follows: (1) The design and development of the learning video media received an evaluation score of 92.50% (excellent) from instructional design experts. (2) The quality of the learning video was assessed as follows: content expert evaluation scored 90% (excellent), instructional design expert evaluation scored 91.66% (excellent), learning media expert evaluation scored 91.66% (excellent), individual testing scored 92.50% (excellent), and small group testing scored 90.83% (excellent). (3) The t-test results showed a t-value of 2.07, with a critical t-value of 1.71 for 23 degrees of freedom at a 5% significance level (α = 0.05). Since t-value exceeds the t-table value, the null hypothesis (H₀) is dismissed, and the alternative hypothesis (H₁) is supported. Consequently, the findings of this research demonstrate that the use of problem-based learning video media proves to be an effective method for teaching the "Harmony in Ecosystems" topic within the Natural and Social Sciences (IPAS) curriculum for fifth-grade elementary school students.